Meningkatkan Pengendalian Penyimpangan Sosial Melalui Pembelajaran Berdasarkan Masalah Siswa SDN 30 Rumaju - Paembonan, Nurhasni Rabia (JURKAM: Jurnal Konseling Andi Matappa, 2018)
This classroom action research aims to help improve the competence of grade 6 students at SD Negeri 30 Rumaju, Luwu Regency, in the case of improving Social storage control. The approach used is a qualitative approach with classroom action research conducted in three stages, namely preparation, implementation and evaluation and reflection, and carried out in at least two cycles. In the preparation phase, scenarios of activities, timelines, places and other supporting facilities such as observation sheet, and questionnaire are prepared. The results showed that 1) Problem-based learning model in IPS lesson can improve both academic or cognitive achievement and attitude change (affective). Increased cognitive ability can be seen in the improvement of learning outcomes that are significant between cycle I with Cycle II that is from the average value of 64.07 to 73.10. 2) Qualitatively there is a change in the attitude of students by doing positive activities in the form of increasing attention, motivation, and interest of students to IPS lesson especially understanding of control of social deviation. Democratic attitudes and cooperation between students become better with the lack of group barriers as they existed before the implementation of this learning model.